Self-Directed Learning and Consensus Decision-Making in the Co-Creation of Virtual Worlds Promoting Student Mental Health Through Mobile Technology Use: A Scoping Review - Carol Nash (Virtual Worlds)
Mobile technology advancements have led to cellphone bans in some school jurisdictions. The basis of these bans is judging their utilization by students as unhealthy, antisocial, and educationally controversial. Banning student cellphones neglects the positive mental health of cellphone use that comes from self-directed learning in students using them in the co-creation of virtual worlds through online communities. This scoping review examines peer-reviewed research from 2021–2025 demonstrating positive mental health value in self-directed mobile technology use through co-creating virtual worlds. The searches are of seven primary databases and one supplementary database, using the keywords “self-directed learning AND mobile technology AND co-creation AND virtual worlds”. Excluded are reviews, book chapters, abstracts, and conference proceedings. The assessment of the findings is that cellphone use promotes a combination of self-directed learning and consensus decision-making, and provides mental health benefits when virtual worlds are co-created by students permitted their use. Appraising these results—regarding self-directed learning, consensus decision-making, and student mental health—the conclusion is that in contemplating the school cellphone use of mobile technology, educators rethink banning their classroom use. The aim would be to support the co-creation of virtual worlds to promote increased self-direction, consensus decision-making, and positive mental health.